2021
DOI: 10.3390/toxics9100243
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorodiphenyltrichloroethane and the Adrenal Gland: From Toxicity to Endocrine Disruption

Abstract: Endocrine disruptors are exogenous compounds that pollute the environment and have effects similar to hormones when inside the body. One of the most widespread endocrine disruptors in the wild is the pesticide dichlorodiphenyltrichloroethane (DDT). Toxic doses of DDT are known to cause cell atrophy and degeneration in the adrenal zona fasciculata and zona reticularis. Daily exposure in a developing organism to supposedly non-toxic doses of DDT have been found to impair the morphogenesis of both the cortex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Additionally, Rachid et al (2016) reported that methomyl administration to pregnant female rats induced similar histological changes in the adrenal gland of rat fetuses. Timokhina et al (2021) illustrated that DDT led to toxic and disruptive effects on the adrenal glands including cell atrophy and degeneration in the adrenal ZF and ZR. This may be due to the ability of pesticides to cross the placental barrier so that they can enter the fetal circulation and inhibit fetal adrenocorticotrophic hormone (ACTH) secretion (Lindhe et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Rachid et al (2016) reported that methomyl administration to pregnant female rats induced similar histological changes in the adrenal gland of rat fetuses. Timokhina et al (2021) illustrated that DDT led to toxic and disruptive effects on the adrenal glands including cell atrophy and degeneration in the adrenal ZF and ZR. This may be due to the ability of pesticides to cross the placental barrier so that they can enter the fetal circulation and inhibit fetal adrenocorticotrophic hormone (ACTH) secretion (Lindhe et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Rachid and Yousef (2013) reported that pregnant rats injected with methomyl showed many pathological changes in the adrenal glands and ovary. The study of Timokhina et al (2021) indicated the severe effects low doses of pesticide exposure on the prenatal and postnatal development, in addition to the disruption of the growth and function of the adrenal glands.…”
mentioning
confidence: 99%
“…A link between malaria insecticides and breast cancer has been shown in early studies examining DDT exposure. DDT is a well-known organochlorine that was once a widely used insecticide used for indoor residual spraying and sprayed extensively in agriculture and populated areas until banned in many countries after being discovered to be an endocrine disrupter [30,31]. Decades later, several studies using Child Health and Development data have shown that DDT exposure to high levels during childhood through early adolescence may contribute to the risk of breast cancer [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…While octyl phenol causes changes in the regions of the cortex medulla, cytoplasmic decomposition in cortex cells, and hemorrhage in the tissue interface of pregnant rats ( 179 ). DDT, a widespread ED causes cell atrophy and degenerative effects in the adrenal cortex mainly in the zona fasciculate and zona reticularis ( 191 ). DDT can bio-accumulate in the thymus, brain, and even in adipose tissue, and induces impairments of both cortex and medulla of the adrenal gland, disrupting hormonal secretion in cortical and chromaffin cells as well as suppressing the thyroxine hydroxylase production in chromaffin cells ( 191 ).…”
Section: Effects Of Mps Nps and Their Associated Chemicals On The Adr...mentioning
confidence: 99%